Kompetence ideálního jazykového lektora na základě subjektivních názorů lektorů a účastníků jazykového vzdělávání - Jandová, Daniela (Univerzita Karlova, Pedagogická fakulta, 2023)
This thesis deals with the current issue of strengthening and creating a competency model for private language teachers. At the present time, it is a very frequently discussed topic in the teacher community, especially given that the requirements for the profession are not specifically defined. Therefore, foreign language teachers often shape their own perception of necessary qualifications of a private language teacher. The aim of this thesis is to develop a competency model of an ideal language teacher based on the subjective opinions of the teachers themselves and language learners and to raise awareness of the requirements for the profession. The theoretical part first describes the position of language education in the context of lifelong learning, then it deals with the issue of competencies with a focus on the language teacher and last but not least it revolves around the language learner. A section is also devoted to the current state of knowledge and the results of research studies on the competencies of language teachers both in Czech and foreign context. The empirical part is based on semi-structured interviews with private language teachers and private language learners from four different age categories. The aim is to describe how students and teachers themselves perceive the ideal. Předložená práce se zabývá aktuální problematikou posilování a vytváření kompetenčního modelu soukromých jazykových lektorů. V současné době se jedná o velmi často probírané téma v lektorské komunitě, i vzhledem k tomu, že nároky na toto povolání nejsou nijak konkrétně stanoveny. Lektoři cizích jazyků si tedy mnohdy představu o svých potřebných kvalifikacích dělají sami. Cílem této diplomové práce je sestavit kompetenční model ideálního jazykového lektora na základě subjektivních názorů samotných lektorů a účastníků jazykového vzdělávání a zvýšit povědomí o náročnosti této profese. Teoretická část nejprve popisuje pozici jazykového vzdělávání v kontextu celoživotního vzdělávání, poté se věnuje problematice kompetencí ...